Gene Expression Markers for Predicting Response to Chemotherapy (2010)
The present invention provides sets of genes the expression of which is important in the prognosis of cancer. In particular, the invention provides gene expression information useful for predicting whether cancer patients are likely to have a beneficial treatment response to chemotherapy. FHIT; MTA1; ErbB4; FUS; BBC3; IGF1R; CD9; TP53BP1; MUC1; IGFBP5; rhoC; RALBP1; STAT3; ERK1; SGCB; DHPS; MGMT; CRIP2; ErbB3; RAP1GDS1; CCND1; PRKCD; Hepsin; AK055699; ZNF38; SEMA3F; COL1A1; BAG1; AKT1; COL1A2; Wnt.5a; PTPD1; RAB6C; GSTM1, BCL2, ESR1; or the corresponding expression product, is determined, said report includes a prediction that said subject has a decreased likelihood of response to chemotherapy.